2017
DOI: 10.1007/s11926-017-0657-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Variability in Systemic Lupus Erythematosus: What We Learned from Genome-Wide DNA Methylation Studies

Abstract: Purpose of Review DNA methylation has emerged as an important contributing factor in the pathogenesis of systemic lupus erythematosus (SLE). Here, we describe the DNA methylation patterns identified in SLE and how these epigenetic changes can influence disease susceptibility, clinical heterogeneity, and disease flares. Recent Findings Several genome-wide DNA methylation studies have been recently completed in SLE. Important observations include robust demethylation of interferon-regulated genes, which is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 54 publications
(86 reference statements)
3
41
1
Order By: Relevance
“…EZH2 overexpression has been linked to increased invasiveness in a number of malignancies, and EZH2 inhibitors are currently being evaluated in clinical trials for cancer therapy (7). Our data indicate that inhibiting EZH2 might be of therapeutic potential in lupus, suggesting the possibility of pharmacologic repurposing of EHZ2 4 inhibitors as a therapeutic option for lupus. In this study, we first examined EZH2 expression patterns in other immune cell types isolated from the peripheral blood of lupus patients, and then tested the effects of using an EZH2 inhibitor in the lupus-prone MRL/lpr mouse model, utilizing both preventative and therapeutic approaches.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…EZH2 overexpression has been linked to increased invasiveness in a number of malignancies, and EZH2 inhibitors are currently being evaluated in clinical trials for cancer therapy (7). Our data indicate that inhibiting EZH2 might be of therapeutic potential in lupus, suggesting the possibility of pharmacologic repurposing of EHZ2 4 inhibitors as a therapeutic option for lupus. In this study, we first examined EZH2 expression patterns in other immune cell types isolated from the peripheral blood of lupus patients, and then tested the effects of using an EZH2 inhibitor in the lupus-prone MRL/lpr mouse model, utilizing both preventative and therapeutic approaches.…”
Section: Introductionmentioning
confidence: 76%
“…DNA methylation plays a critical role in the pathogenesis of lupus (3). Abnormal DNA methylation patterns have been described in multiple immune cell types isolated from lupus patients, and a role for genetic-epigenetic interaction in the pathogenesis of lupus has been suggested (4). Further, abnormal DNA methylation patterns in lupus have been shown to contribute to clinical heterogeneity, disease variability between ethnicities, and lupus flare and remission (4).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic dysregulation plays an important role in the pathogenesis of lupus [3]. While most epigenetic studies in lupus have been performed in T cells, there is evidence to suggest reduced DNA methylation levels in multiple cell types in this disease.…”
mentioning
confidence: 99%
“…This indicates an 'epi' genetic component to the etiopathogenesis of these diseases. Studies in SLE, RA, Sjogren's syndrome, scleroderma and recently vasculitis have suggested and confirmed this fact [3][4][5][6]. However, we are still in need of studies on Ax SpA where the strong association with a gene (HLA B27) was revealed almost 3 decades ago [7] and yet, the exact association between the HLAB27 gene and Ax SpA still remains unexplained.…”
Section: Introductionmentioning
confidence: 97%